2020
DOI: 10.1111/ijpo.12712
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal and paternal feeding styles of infants in a racially diverse US birth cohort

Abstract: Summary Background Maternal feeding style has been associated with childhood obesity and has been the target of numerous interventions, but few studies included fathers. Objectives We assessed correlations and associations between maternal and paternal feeding style. Methods We examined 202 mothers, fathers, and infants in Nurture, a racially diverse US cohort (2013‐2017). Mothers and fathers completed the Infant Feeding Style Questionnaire when infants were 6 and 12 months. We examined unadjusted correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The remaining 16 studies included NMCs and mothers. Nine examined the two types of caregivers for similarities and differences [ 28 , 29 , 31 , 35 , 43 , 47 , 52 , 59 , 60 , 63 ]. The remaining seven studies examined the two types of caregivers as one group [ 23 , 27 , 32 , 39 , 41 , 53 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 16 studies included NMCs and mothers. Nine examined the two types of caregivers for similarities and differences [ 28 , 29 , 31 , 35 , 43 , 47 , 52 , 59 , 60 , 63 ]. The remaining seven studies examined the two types of caregivers as one group [ 23 , 27 , 32 , 39 , 41 , 53 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies provided information on feeding styles, measured quantitatively. In their study of mothers and fathers of infants in the U.S., Benjamin-Neelon and Neelon [ 29 ] used the Infant Feeding Style Questionnaire (IFSQ) [ 69 ] which measures five styles, one of which is the responsive style. They found that fathers scored higher than mothers on the pressuring and laissez-faire styles and maternal and paternal feeding styles were correlated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation